The Mediating Effect of Depression and Interpersonal Contact on the Association Between Cognitive Function and Activities of Daily Living Among Older Adults with Dementia in South Korea: The 2020 Korea Elderly Survey - Kawoun Seo; Sun Ae Kim; Myoungjin Kwon (Psychiatry International)
This study aimed to investigate the mediating effects of depression and interpersonal contact on the association between cognitive function and activities of daily living (ADL) in older adult patients with dementia. This descriptive cross-sectional study used the 2020 Korea Elderly Survey and included 189 older adults aged 65 years who were diagnosed with dementia by a physician. The analysis involved descriptive statistics and correlation analysis with Statistical Package for the Social Sciences (SPSS) version 24.0, and the dual mediation effect was analyzed with PROCESS Macro for SPSS version 3.5 Model 6. Cognitive function was negatively related to both ADL and depression but positively correlated with interpersonal contact. ADL exhibited positive and negative correlations with depression and interpersonal contact, respectively. Cognitive function significantly affected ADL and depression. Cognitive function significantly affected interpersonal contact, but depression was not significant. Finally, cognitive function exhibited a significant effect on ADL, but depression and interpersonal contact were not significant. Cognitive function showed the greatest effect on ADL in older adults diagnosed with dementia. Therefore, a program to prevent cognitive decline in older adults with dementia needs to be developed. Additionally, further studies are warranted to investigate the factors that affect the association between cognitive function and ADL in older adults with dementia.